Analysis Of The Impacts Of Infrastructure On The Economic Growth Pasangkayu Regency - Pusmahasib Pusmahasib; Rahmatia Rahmatia; Kurniaty Kurniaty (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The economic growth of Pasangkayu regency experienced fluctuations between 2016 and 2020. Roads and Electricity of economic infrastructure and Education and Health of social infrastructure were assumed to have an influence on the growth of Gross Regional Domestic Product (GRDP). No preliminary research has been found examining the interrelationships of infrastructures with economic development, particularly in Pasangkayu Regency. The purpose of this research is to see the influence of road, electricity, education, and health on economic growth in relation to GRDP. Secondary data collection from BPS Pasangkayu Regency and BPS West Sulawesi Province was carried out from 2010-2020. Classical assumption methods such as normality, autocorrelation, multicollinearity, and heteroskedasticity tests were met in this study so that multiple linear regression tests such as t-tests, f-tests, and R2 were performed. The results of this research show that the entire economic infrastructure (Road Infrastructure p-value 0.213; Electricity Infrastructure p-value 0,643) and social infrastructure (Education Infrastructure p-value 0.094; Health Infrastructure p-value 0.651) simultaneously and partially has no effect on the economic growth of Pasangkayu regency. The increasing provision of Road, Electricity, Education and Health infrastructures is not in line with the increase in GRDP of Pasangkayu Regency which experienced negative growth in the ten-year period.